2015
DOI: 10.1139/apnm-2015-0241
|View full text |Cite|
|
Sign up to set email alerts
|

Supplementation with a proprietary blend of ancient peat and apple extract may improve body composition without affecting hematology in resistance-trained men

Abstract: Adenosine-5=-triphosphate (ATP) is primarily known as a cellular source of energy. Increased ATP levels may have the potential to enhance body composition. A novel, proprietary blend of ancient peat and apple extracts has been reported to increase ATP levels, potentially by enhancing mitochondrial ATP production. Therefore, the purpose of this investigation was to determine the supplement's effects on body composition when consumed during 12 weeks of resistance training. Twenty-five healthy, resistance-trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…There was also a significant increase in whole-body lean mass between groups over time, which only increased over time in the present study. Moreover, the present results concerning muscle mass are consistent with the observations of supplementation with ancient peat and apple extracts without caffeine [ 24 ]. Wilson et al [ 44 ] reported no interactions for all measured blood markers, while the present study observed a possible effect for creatinine and eGFR, yet the relevance of these observations may be undue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was also a significant increase in whole-body lean mass between groups over time, which only increased over time in the present study. Moreover, the present results concerning muscle mass are consistent with the observations of supplementation with ancient peat and apple extracts without caffeine [ 24 ]. Wilson et al [ 44 ] reported no interactions for all measured blood markers, while the present study observed a possible effect for creatinine and eGFR, yet the relevance of these observations may be undue.…”
Section: Discussionsupporting
confidence: 92%
“…The precise methods of the present study have previously been published with the exception of a difference in treatment [ 24 ]. Subjects were randomly assigned to either the PLA ( n = 11) or TRT ( n = 10) groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent supplement on the market is ancient peat and apple extract, which is sold under the label of "elevATP". This supplement has been shown to increase blood levels of ATP [22], increase exercise levels in sedentary individuals from a single dose [23], and enhance responses to chronic resistance training [24]. The supplement Huperzine has been shown to have positive effects on brain function, specifically decreasing cognitive deficits and oxidative stress in the rodent model after hypobaric hypoxia [25], and has been shown in conjunction with other supplements to enhance upper body strength endurance performance [6] and anaerobic sprint performance [26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these observations, supplementation for indirect ATP enhancement is yet to be evaluated for potential to augment performance in response to resistance training. However, the existing data on ancient peat and apple extracts for increasing both whole blood and muscle ATP levels [ 8 , 9 ] and muscle mass [ 16 ] support the plausibility for chronic supplementation yielding positive augmentation of performance following resistance training. Therefore, the purpose of this study is to determine the effects of a proprietary blend of ancient peat and apple extracts on athletic performance.…”
Section: Introductionmentioning
confidence: 99%